2022
DOI: 10.3390/cli10090133
|View full text |Cite
|
Sign up to set email alerts
|

Compound Extremes of Air Temperature and Precipitation in Eastern Europe

Abstract: The spatial distribution of compound extremes of air temperature and precipitation was studied over the territory of Eastern Europe for the period 1950–2018. Using daily data on air temperature and precipitation, we calculated the frequency and trends of the four indices—cold/dry (CD), cold/wet (CW), warm/dry (WD) and warm/wet (WW). The connection between these indices and large-scale patterns in the ocean–atmosphere system, such as the North Atlantic Oscillation (NAO), the East Atlantic (EA) and Scandinavia (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 79 publications
1
3
0
Order By: Relevance
“…The continuous increase in air temperature contributes to an increase in the frequency of extremes in many parts of the globe. Previously, it was shown that negative trends for cold indices were found in Eastern Europe, and positive trends were found for warm ones [55]. Similar trends are typical for most regions of the globe [56][57][58].…”
Section: Discussionsupporting
confidence: 66%
“…The continuous increase in air temperature contributes to an increase in the frequency of extremes in many parts of the globe. Previously, it was shown that negative trends for cold indices were found in Eastern Europe, and positive trends were found for warm ones [55]. Similar trends are typical for most regions of the globe [56][57][58].…”
Section: Discussionsupporting
confidence: 66%
“…Since the 1980s, the NAO and MOI have exhibited large year-to-year variability ( Figure A1 ) [ 26 , 67 , 88 ]. The summer SCAND has shown a mostly negative linear trend since the mid-20th century [ 113 ], but its inter-annual variation increased since the 1990s [ 114 ]; thus, this trend in the late summer SCAND is no longer valid ( Figure A1 ). A lack of significant long-term trend in the overall passage (AA) at Hel ( Figure 3 A), which was influenced by the spring MOI and the late summer SCAND in the previous year ( Figure 4 B), is consistent with no long-term trends in both these climate indices ( Figure A1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite signi cant progress in understanding compound extremes, their linkage over the western U.S. to major climate modes is still unclear. Several recent studies have investigated relationships between compound extremes and climate modes of variability, but the analysis was mainly focused on interannual timescales related to impacts from the North Atlantic Oscillation (NAO) and El Niño/Southern Oscillation (ENSO) 7,24,25,26 . ENSO is the main source of seasonal climate predictability around the world and particularly over North America 65,66 .…”
Section: Introductionmentioning
confidence: 99%